(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Watermelon (Citrullus lanatus) rind often discarded as agricultural waste, contains valuable bioactive compounds such as citrulline, phenolics and flavonoids. This study investigates the impact of solvent polarity on the efficiency and phytochemical profile of watermelon rind extracts using ultrasound-assisted extraction (UAE). Extractions were performed with ethanol, ethyl acetate, and hexane under fixed conditions (30°C, 70 minutes, 1:10 solid-to-liquid ratio). Extracts were analyzed for total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity using the DPPH radical scavenging assay. Ethanol yielded the highest TPC (4.47 ± 0.03 mg GAE/g) and antioxidant activity (IC50: 4.56 μg/mL), while ethyl acetate exhibited the highest TFC (1.292 ± 0.02 mg QE/g) with comparable antioxidant potential. The results demonstrate that solvent polarity significantly affects the recovery of bioactive compounds, with ethanol and ethyl acetate efficiently extracting hydrophilic and moderately lipophilic constituents. By demonstrating that watermelon rind may deliver high antioxidant recovery utilizing UAE, this study demonstrates its potential as a value-added source rather than a waste product. When combined with UAE, ethanol excels out as a safe and practical green solvent, presenting a scalable and environmentally responsible approach to develop watermelon rind into useful ingredients for food, nutraceutical, and cosmetic applications.